If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (29x + -3) = (15x + 7) Reorder the terms: (-3 + 29x) = (15x + 7) Remove parenthesis around (-3 + 29x) -3 + 29x = (15x + 7) Reorder the terms: -3 + 29x = (7 + 15x) Remove parenthesis around (7 + 15x) -3 + 29x = 7 + 15x Solving -3 + 29x = 7 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -3 + 29x + -15x = 7 + 15x + -15x Combine like terms: 29x + -15x = 14x -3 + 14x = 7 + 15x + -15x Combine like terms: 15x + -15x = 0 -3 + 14x = 7 + 0 -3 + 14x = 7 Add '3' to each side of the equation. -3 + 3 + 14x = 7 + 3 Combine like terms: -3 + 3 = 0 0 + 14x = 7 + 3 14x = 7 + 3 Combine like terms: 7 + 3 = 10 14x = 10 Divide each side by '14'. x = 0.7142857143 Simplifying x = 0.7142857143
| 7x+8+40+90=180 | | 22+4x+1+18+7.5=180 | | 11x+10y=25 | | 6s^2=15+27s | | 3/4-2x-1/5(x-10) | | 5-3(x-2)=-5x+8 | | 7/2(14) | | 4s+20=3s+42s | | 62+43+8x-5=180 | | 7(5p-6)-3=130 | | .49s+.21(s-5)=7.35 | | 2.5+.5m=1+.75m | | 0.1r-0.05+0.5r=-0.026 | | 6-18x+18=-30 | | (8x-31)=(6x+3) | | (3-3)3x+7=2x | | 3x+2x+4=1 | | -88=-2(2+7x)+2x | | -(8x-1)-8=-7x-(x+9) | | 5m-8=-4-3 | | x/1/8=4/1/1/2 | | 8t-3t-2t-t-2=16 | | 20i/(1-3i) | | .5a+.375=.75 | | 12+2m=7[m+6] | | 554/730 | | 2l+2(l-25)=82 | | 5x^2-250x+5000=0 | | 90=4x+8 | | (9x+2)=133 | | a*.2+a=75 | | 5x+9.9=4.8+8w |